And the ocean was our sky - Ness, Patrick, 1971- (HarperTeen, an imprint of HarperCollinsPublishers, 2018)
Presents a twist on themes from Moby Dick in the story of a proud warrior whale pod that attacks a ship before pursuing a near-mythical adversary on a vengeful hunt that risks the worlds of both whales and humans.